EFFECT OF ADENOSINE 3'-5'-CYCLIC MONOPHOSPHATE ON CELL PROLIFERATION - Froehlich, Jeffrey E. (The Rockefeller University Press, 1972)
Secondary cultures of human diploid fibroblasts, which demonstrate density-dependent inhibition of cell growth, were used to study the effect of adenosine 3'-5'-cyclic monophosphate (cAMP) on cell proliferation. DNA synthesis in nonconfluent cultures and in contact-inhibited cultures stimulated to grow by refeeding with fresh medium was found to be inhibited by exogenous cAMP. The properties of this inhibition of DNA synthesis, together with the alterations in cAMP metabolism observed in confluent cultures of cells stimulated with fresh medium to resume growth, strongly suggest that cAMP is involved in contact-inhibition of cell proliferation.